Nasal Septal Perforation Reconstruction With Superior-Based Pedicled Nasolabial Island Flap in a Patient With the Raynaud Phenomenon. Issue 3 (May 2015) - Keles, Musa Kemal; Cepni, Hakan; Cicekci, Faruk; Yenigün, Alper
<x xml:space="preserve">Abstract</x> Abstract Perforation of the nasal septum may have multiple causes, and there are lots of options for reconstruction. We discuss a septal perforation case with Raynaud phenomenon.